Utilization Optimization of Capacitive Pulsed Power Supply in Railgun - Genrong Cao; Hongjun Xiang; Zhiming Qiao; Chunyan Liang; Xichao Yuan; Jin Wang; Bin Lei (Energies, 2022)
The excitation pulse current used to drive the railgun needs to present very a high magnitude (hundreds of kA) flat-top with very low ripple. At present, the main method to obtain this current is to increase the number of the capacitive pulsed power supply (PPS) modules. However, low utilization and massive volume of the railgun system would occur with this method, hampering the application of railgun. Therefore, the utilization optimization technology of PPS is researched in this paper. In order to obtain highly stable flat-top current, the control strategy of the capacitive PPS is designed, and a new charging voltage configuration is proposed, which significantly decreases the use of the capacitive modules. Besides, a miniaturization transformation scheme of capacitive PPS is proposed based on the control strategy. The result shows that the flat-top current ripple has the biggest influence on the PPS utilization, and the smaller the flat-top current ripple, the lower the utilization. When the current with 200 kA magnitude and 0.75% flat-top current ripple is achieved, an 81.9% decrease of volume and a 428.7% utilization improvement are achieved through miniaturization transformation.